Analisis Kinerja Keuangan Perusahaan Pariwisata dan Hotel di BEI Tahun 2022–2025 dengan Current Ratio, Net Profit Margin, dan Harga Saham - Maryola Maryola; Suryanto Sosrowidigdo; Siti Nurjanah (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the financial performance of issuers in the tourism and hospitality subsectors listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period using the Current Ratio (CR), Net Profit Margin (NPM), and stock price as indicators. The study was motivated by the post-COVID-19 pandemic recovery and inconsistent findings from previous studies regarding the relationship between liquidity, profitability, and stock prices. This study employed a descriptive quantitative approach using secondary data in the form of annual financial reports published by the IDX. The sample was selected using purposive sampling, involving 10 companies and producing 40 observations over the four-year study period. The results showed that the average Current Ratio of most sampled companies was above the ideal standard of 200%, indicating a highly liquid condition. Meanwhile, Net Profit Margin demonstrated gradual recovery from negative conditions during the pandemic toward more positive and stable values in 2024–2025. Stock price movements also tended to develop in line with improvements in Current Ratio and Net Profit Margin. These findings indicate that sound liquidity and profitability conditions can strengthen investor confidence and support stock price increases. Therefore, effective liquidity and profitability management is an important factor in improving financial performance and investment attractiveness in the tourism and hospitality subsectors.